PERENCANAAN SEKOLAH DASAR BERBASIS SEKOLAH ALAM DENGAN PENEKANAN EFEK BAYANGAN TERHADAP BANGUNAN DI KOTA SAMARINDA - Putra, Eka; Risnawaty, Mahdalena; Riza, Ahmad (Jurnal Totem : Architecture, Environment, Region and Local Wisdom, 2020)
School of nature is a school built for efforts to develop education carried out by learning methods in nature directly. The purpose of this study is the application of shading effects to natural school-based elementary school buildings. In the natural school-based primary school planning process with emphasis on the shading effect of buildings in Samarinda City there are several stages, namely the data collection stage, the analysis phase and the concept stage in building design. The resulting shading effects can reduce human discomfort with sunburn.The analysis results show the amount of space with an area of building base coefficient of 2,309 m2, area of the green base coefficient of 23,090 m2. By dividing 29 rooms from 11 buildings. The location of the site is on Jl. P.Suryanata, Perumahan Bukit Pinang. In the concept of buildings hexagon-shaped so that spatial planning in each building can be fully utilized. In the concept of shading effect with the method of using roof eaves, the use of secondary skin, regulating the distance between buildings, and the use of shade trees.Â Keywords: School of nature, shading effects, SamarindaÂ